Estágio menopausal e níveis hormonais no desempenho muscular e funcional em mulheres de meia idade: um estudo transversal - Matos, Gabrielle Silveira Rocha (2014)
Introduction: Hypoestrogenism is the main characteristic of female aging. It promotes significant changes in body composition, both in fat mass as in lean body mass, leading to a decrease in muscle strength and physical performance. Objective: The aim of this study was to test whether menopausal status and hormone levels are associated with muscular strength and physical performance in middle-aged women. Methods: In a cross-sectional study it was collected sociodemographic data, gynecological history, anthropometric and biochemical measures in women aged 40 to 65 years in Parnamirim-RN. The menopause status (pre, peri and post menopause) was determined by menstrual history. All women underwent three dimensions of physical performance assessment: handgrip dynamometry, gait speed and chair stands test - Short Physical Performance Battery (SPPB). Categorical data were presented as absolute and relative frequencies. Quantitative data were showed as mean and standard deviation and the normality of distribution was verified with Kolmogorov-Smirnov (KS) test. Biochemical measures of estradiol and follicle-stimulating hormone (FSH) were transformed to log10. ANOVA with Tukey post-test for comparison of variables between the groups pre, peri and post-menopausal was performed and then multiple linear regression analyzes. Results: Two hundred and seventy eight women aged 50.2 (±5.58) years composed this study, being 50 women in premenopausal status (18%), 122 in perimenopausal (43.9%), and 106 postmenopausal stage (38.1%). The groups were different in age (p=0.001), marital relationship duration (p <0.001), number of pregnancies (p=0.001) and parity (p=0.001). Differences in biochemical measures were observed among the groups: estradiol (p<0.001), FSH (p<0.001), total cholesterol (p=0.001). There were no differences in gait velocity between menopausal status. Values in mean of grip strength decreased by postmenopausal women to perimenopausal and premenopausal ones (24.5 ± 5.1, 25.6 ± 5.4, 26.9 ± 4.9 for post-stage, pre and peri menopausas, respectively, p = 0.02) and the performance of chair stands test was better in premenopausal women compared with that in peri and postmenopausal status (p = 0.02). In multiple linear regression for muscle strength, the variables that remained were: age, estradiol and somatic symptoms measured by Menopause Rating Scale-MRS (R2=0.15). While for the xiv chair-stands test the predictors were number of births and FSH values (R2=0.04). Conclusion: There is a relationship between the stages of menopause and muscle performance in measures of grip strength and sit-up test and these are influenced by the fall of estrogens levels. Data suggest that the decrease in muscle strength and physical performance already appear in the transition to menopause stage, pointing to the need for more research in this area and appropriate preventive interventions